Analysis of the Relationship between Parenting Style and the Risk of Depression in Teenager - Supartini, Yupi; Ningsih, Ratna; Vernan, Rizka Rayharani Islami (Poltekkes Kemenkes Jakarta III, 2023)
Background : Depression is an emotional state usually characterized by extreme sadness, feelings of worthlessness and guilt. Depression in adolescents requires support from parents for adolescents to be able to overcome it as well. Parents with a democratic parenting style will make the child's personality self-controlled and good with his friends. Purpose : This study was to analyze the relationship between parenting style and the risk of depression. Methods : This study used a descriptive analysis research design with a cross sectional approach. The sample in this study was 102 students grade 11 and data analysis used the chi square test. Results : The results of the analysis showed that the relationship between parenting style and the risk of depression was found to be p = 0.000 (p <0.05). Based on the results of the analysis in this study, it can be concluded that there is a significant relationship between parenting style and the risk of depression in adolescents